Analisis Tingkat Kedisiplinan Ustaz dan Ustazah dalam Membangkitkan Motivasi Belajar Santri di TPQ Darussalam Desa Bandung Kecamatan Kebumen - Khusna, Malika; Faisal, Faisal (IAINU Kebumen, 2025)
This research aims to determine the level of discipline of ustaz and ustazah in generating student motivation to learn at TPQ Darussalam, Bandung Village, Kebumen District. This research is quantitative research. Data collection in this research was through observation techniques, questionnaires, and documentation. The data analysis techniques used are descriptive analysis and inferential statistical analysis. The results of this research show that the level of discipline of ustaz and ustazah in generating students' learning motivation is 35.6%. This can be proven through simple linear regression testing in the model summary table in the R-Square column. Through class interval testing, the discipline of ustaz and ustazah as well as the learning motivation of students at TPQ Darussalam Bandung Village, Kebumen District are included in the good category